Airplane Waste Disposal System Tank Designing Using Numerical Simulation and Experimental Bench Results - Medvediev S. V.; Lantin D. H. (Журнал інженерних наук)
Modern passenger aircraft cannot be considered without the requirements to ensure the safety and comfort of passengers on board. One of the systems that provide the necessary comfort on the plane is the waste disposal system, which is designed to meet the physiological needs of the human body. Today, a promising waste disposal system type is a vacuum principle of operation. The vacuum-type waste disposal system is a combination of complex multifunctional subsystems: waste collection, waste storage, vacuumization, drain and flush, system control. Such systems development, consisting of devices, based on heterogeneous physical principles of operation, is a complex scientific and technical problem associated with the conduct of diverse applied research in the field of design, development and targeted use of the system. One main system elements is a waste storage tank. An important step in the tank design is to determine its weight and size characteristics in the early stages of development. These characteristics are significantly influenced by the tank filling process, which also determines the placement of equipment in it. The aim of the work presented in the article is to study the tank filling process with the help of numerical simulation methods.